Prevalence of dental caries and associated factors of detention center inmates in South Korea compared with Korea National Health and Nutrition Examination Survey (KNHANES) respondents: a retrospective study - Ilkwang Hwang; Kyungtaek Park; Hee-Kyung Park (BMC, 2022)
Abstract Background Correctional institution inmates have reduced access to dental care; however, a quantitative assessment of their oral health condition has not yet been performed in South Korea. Therefore, this study aimed to assess dental caries and compare the prevalence of dental caries and associated factors between inmates and the general South Korean population. Methods The dental records of two detention centers in South Korea were retrospectively analyzed to assess the clinical oral health condition of inmates using the Decayed, Missing, and Filled Teeth (DMFT) index and self-reported questionnaire. These data were compared with similar data obtained from the Korea National Health and Nutrition Examination Survey (KNHANES) for the general South Korean population. Results In total, 642 inmates were analyzed and compared with 13,345 KNHANES participants in the KNHANES. The inmate and KNHANES groups demonstrated significant intergroup differences, with a higher prevalence of untreated caries, DMFT, decayed teeth (DT), and missing teeth (MT) values among the inmates. The prevalence of untreated caries decreased according to the history of dental pain in the inmate group but increased in the KNHANES group. The decrease in DMFT with a history of dental pain was significant only in the inmate group. Furthermore, self-rated oral health was significantly associated with prevalence of untreated caries, DMFT, DT, MT, and filled teeth (FT) in the inmate group but with prevalence of untreated caries, DMFT, DT, and MT in the KNHANES group. It was found that this is because there is an interaction effect by the group. Conclusions The oral health of the inmate group was significantly poorer than that of the general group. Since DMFT, DT, MT, and FT values and prevalence of untreated caries in the inmate group were significantly related to their self-rated oral health, suggesting that self-rated oral health should be incorporated into the dental health screenings of correctional institution inmates.